2019
DOI: 10.7333/1909-0702015
|View full text |Cite
|
Sign up to set email alerts
|

Time-Efficient Adaptive Measurement of Change

Abstract: The adaptive measurement of change (AMC) refers to the use of computerized adaptive testing (CAT) at multiple occasions to efficiently assess a respondent's improvement, decline, or sameness from occasion to occasion. Whereas previous AMC research focused on administering the most informative item to a respondent at each stage of testing, the current research proposes the use of Fisher information per time unit as an item selection procedure for AMC. The latter procedure incorporates not only the amount of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Items that are too time consuming are less preferred even if they are informative. Research has demonstrated that given a time limit, using MIT for item selection can yield more efficient CAT, leading to smaller measurement errors (Fan et al 2012, Finkelman & Wang 2019).…”
Section: Efficient Item Selection In Computerized Adaptive Testingmentioning
confidence: 99%
“…Items that are too time consuming are less preferred even if they are informative. Research has demonstrated that given a time limit, using MIT for item selection can yield more efficient CAT, leading to smaller measurement errors (Fan et al 2012, Finkelman & Wang 2019).…”
Section: Efficient Item Selection In Computerized Adaptive Testingmentioning
confidence: 99%
“…To broaden the applicability of methods focused on improving CAT delivery in terms of DTE, Cheng et al (2017) further modified the MIT criterion to a simple version (MIT-S) by using the expected logarithm of response time. Recently, the MIT framework was applied to adaptively measure individual change (Finkelman & Wang, 2019) and to calibrate items online (He et al, 2021), and was extended to the context of computerized classification testing (Sie et al, 2015) and cognitive diagnostic computerized adaptive testing (Huang, 2020). The results showed that items selected in the MIT framework saved testing time, ensured satisfactory measurement precision, and produced a higher true positive rate for measuring individual change.…”
Section: Introductionmentioning
confidence: 99%